If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 6y + -4 Reorder the terms: 3x = -4 + 6y Solving 3x = -4 + 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = -1.333333333 + 2y Simplifying x = -1.333333333 + 2y
| 1.4a-3=1 | | sqrt(x-43)-sqrt(t+28)=158 | | 3x/4-8=x/3 | | 2x-7y=15fory | | x^2-36x-252=0 | | 5-1/5x=1/10x | | 11=-15x+7 | | 5(x-4)=3(x+18) | | sqrt(4x+4)=sqrt(-5x-6) | | sqrt(4x+4)=sqrt(2x+2) | | 11=-15m | | (y-12)(y-1)=0 | | -42=6x+6x-6 | | 11=-15x-7 | | 40=(24/4)h | | 4-6m=-2 | | 6[3-(-4x-3)]=72x+108 | | 4x+3=2-8x | | -36t=-8 | | 5b-4=-8 | | 4/12x5/6 | | 36=12b | | 6x+7=-17+2x | | 3(4y-1)-2=8-8.5 | | -1/12x | | .333-.666=1 | | 5/13-2x=(-8/13) | | 2.1x-13.79=4.9 | | .009=0.01 | | -8a^2+72=0 | | .333-.666= | | 5y-2=-6 |